TINGKAT EFISIENSI TEKNIS USAHATANI PADI SAWAH DI DESA TAMBAKJATI, KECAMATAN PATOKBEUSI, KABUPATEN SUBANG, PROVINSI JAWA BARAT - Gina Rahnanita; Nur Syamsiyah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
Subang Regency is the third rice production center in West Java. Rice farming has become the main activity and hereditary in the District Patokbeusi. However, in 2016, Patokbeusi sub-district decreased rice productivity by 1.4 tons/ha. In this study aims to analyze the technical efficiency level of rice farming, and to knew the factors that affect farm productivity. This research was conducted in Tambakjati Village, Patokbeusi Subdistrict, Subang Regency, West Java. Data collection technique was conducted by survey with sampling method to rice farmer, which amounted to 55 people. The design of this studied is quantitative to express the effect of production factors on farming productivity. This research method used analysis of Cobb-douglas production function with stockastic frontier approach to knew the level of technical efficiency. The results showed that the average technical efficiency level of rice farming is 0,037. It means that rice farming in Tambakjati Village has not been efficient in using input production yet, so its use should be added. Production factors that have significant effect (? = 5%) on farming productivity are land, labour, seed, urea, and SP-36.Keywords: Rice farming, technical efficiency, stockastic frontier